Climate Impacts From Large Volcanic Eruptions in a High‐Resolution Climate Model: The Importance of Forcing Structure. Issue 13 (10th July 2019) - Yang, Wenchang; Vecchi, Gabriel A.; Fueglistaler, Stephan; Horowitz, Larry W.; Luet, David J.; Muñoz, Ángel G.; Paynter, David; Underwood, Seth
Abstract: Explosivevolcanic eruptions have large climate impacts and can serve as observable tests of the climatic response to radiative forcing. Using a high‐resolution climate model, we contrast the climate responses to Pinatubo, with symmetric forcing, and those to Santa Maria and Agung, which had meridionally asymmetric forcing. Although Pinatubo had larger global‐mean forcing, asymmetric forcing strongly shifts the latitude of tropical rainfall features, leading to larger local precipitation/tropical cyclone changes. For example, North Atlantic tropical cyclone activity over is enhanced/reduced by SH forcing (Agung)/NH forcing (Santa Maria) but changes little in response to the Pinatubo forcing. Moreover, the transient climate sensitivity estimated from the response to Santa Maria is 20% larger than that from Pinatubo or Agung. This spread in climatic impacts of volcanoes needs to be considered when evaluating the role of volcanoes in global and regional climate and serves to contextualize the well‐observed response to Pinatubo. Key Points: Weaker‐than‐Pinatubo volcanic eruptions with interhemispherically asymmetric forcings can have larger climate impacts than Pinatubo Zonal‐mean and regional precipitation and TC activity are more sensitive to interhemispherically asymmetric than symmetric eruptions Global‐mean surface temperature is more sensitive to the NH asymmetric eruptions